Understanding the Lived Experiences of Transitioning Adults with Gender Dysphoria in the United Kingdom: An Interpretative Phenomenological Analysis. Issue Volume 14:Issues 1(2020) (2nd January 2020) - Harrison, Nicola; Jacobs, Lisa; Parke, Adrian
Abstract: This study aimed to gain an in-depth understanding of the lived experiences of adults with gender dysphoria seeking treatment in the UK. Two transgender males and six transgender females participated. Data were collected via semi-structured interviews and analyzed using Interpretative Phenomenological Analysis. Analysis of the transcripts revealed three superordinate themes: "Accessing Healthcare Services, " "Searching for Acceptance, " and "Impact of Gender Dysphoria on Psychological Wellbeing" that represented the experiences for this population. It is concluded that there is a substantial need for counseling support during and after the treatment-seeking process within the UK. Public significance: This study provides an insider's account of the experience of seeking help and support from peer and familial groups, as well as healthcare providers, as an individual aiming to transition gender in the United Kingdom. This study highlights the feeling of neglect that individuals with Gender Dysphoria can experience when seeking care from the National Health Service (NHS), and the impact that this has on well-being.